THE ROLE OF RAILWAYS IN THE INFRASTRUCTURE OF THE TRANSCASPIAN REGION OF THE TURKESTAN GENERAL GOVERNORATE - Rakhimov Bektosh Elmurodovich (Scholar Express Journal, 2024)
The Turkestan General Governorate, established in 1867, was administratively divided into regions, and each region was administered taking into account its characteristics and location. The Turkestan Governorate, located east of the Caspian Sea, borders Iran and Afghanistan on the north-west Siberian hills and on the south through the Hindukush Mountains. Turkestan is a very fertile field for research in terms of the uniqueness of nature and the culture of its people.
Keywords: Turkestan General Governorate; Caspian Sea; borders Iran and Afghanistan